2013
DOI: 10.1186/1741-7015-11-99
|View full text |Cite
|
Sign up to set email alerts
|

Slow CCL2-dependent translocation of biopersistent particles from muscle to brain

Abstract: BackgroundLong-term biodistribution of nanomaterials used in medicine is largely unknown. This is the case for alum, the most widely used vaccine adjuvant, which is a nanocrystalline compound spontaneously forming micron/submicron-sized agglomerates. Although generally well tolerated, alum is occasionally detected within monocyte-lineage cells long after immunization in presumably susceptible individuals with systemic/neurologic manifestations or autoimmune (inflammatory) syndrome induced by adjuvants (ASIA).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 47 publications
10
122
1
Order By: Relevance
“…Alhydrogel® biopersistence was confirmed in a variety of laboratory animal models up to 6-12 months post-injection, in both the injected muscle (Verdier et al, 2005;Authier et al, 2006;Khan et al, 2013;Eidi et al, 2015) and distant lymphoid organs . Particles traffic from an injected tissue to the dLNs is size-dependent, smaller particles (20-200 nm) being able to drain in a free form whereas medium-sized particles (0.5-2 µm) are exclusively subjected to cell transportation (Manolova et al, 2008).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Alhydrogel® biopersistence was confirmed in a variety of laboratory animal models up to 6-12 months post-injection, in both the injected muscle (Verdier et al, 2005;Authier et al, 2006;Khan et al, 2013;Eidi et al, 2015) and distant lymphoid organs . Particles traffic from an injected tissue to the dLNs is size-dependent, smaller particles (20-200 nm) being able to drain in a free form whereas medium-sized particles (0.5-2 µm) are exclusively subjected to cell transportation (Manolova et al, 2008).…”
Section: Discussionmentioning
confidence: 82%
“…This compound spontaneously forms micron-sized agglomerates (Johnston et al, 2002), subjected to slight size variations after antigen adsorption and in vivo interactions with phosphate, organic acid and proteinaceous environments. A series of recent reports from our laboratory have shown that translocation of aluminium hydroxide may be specifically related to monocyte lineage cell uptake of this poorly biodegradable compound (Khan et al, 2013;Crépeaux et al, 2015;Eidi et al, 2015), likely resulting from phagocytosis or macropinocytosis (Mao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortico-subcortical brain lesions are possibly of inflammatory or toxic origin. Experimental data evidenced that after intramuscular injections of aluminum hydroxide, aluminum particles can translocate into the brain tissue where they remain trapped [10]. However, to our knowledge, there is no pathological or radiological evidence for brain damage specifically associated with MMF.…”
Section: Discussionmentioning
confidence: 89%
“…Aluminium is, of course, a powerful immunogen, being the preferred adjuvant in vaccination and immunotherapy. This activity as an adjuvant, and concomitantly as an antigen, at injection sites in skin or muscle must also be considered for focal accumulations of aluminium within the CNS and such reactivity may underlie aluminium's suggested roles in autoimmunity [3][4][5].…”
Section: Aluminium the Neurotoxinmentioning
confidence: 99%